Analysis of the clinical parameters and management aspects of rhino-maxillary mucormycosis, Part I: challenges in diagnosis - Samir Ali Elborolosy; Ghada Amin Khalifa; Kamal Ebeid; Hamada Mahran; Mohammed Nahed Attia Mohammed; Mohamed Yehia Abdelfattah; Mohamed Mostafa Elshamaa (BMC Oral Health)
Abstract Background Rhinomaxillary mucormycosis (RMM) is frequently missed by clinicians, especially when laboratory testing fails to identify fungi in tissue samples. This challenge results in delayed diagnosis and poor prognosis. Therefore, this study was conducted to clarify challenges in the diagnosis of RMM and its characteristics by developing a protocol-driven multidisciplinary workflow. Methods A retrospective case series study was conducted from June 2022 to January 2024. The study participants were those who had undergone initial RMM screening at Beni-Suef University's oral/maxillofacial or ENT departments. A careful history was obtained, and clinical and endoscopic examinations were performed on each patient. The following investigations were performed: CT scans, contrast-enhanced MRIs, blood analyses, and histological examinations. The RMM diagnosis was categorized into possible, probable, and proven. Descriptive statistics (percentages and means ± SDs) and chi-square tests were used to analyze the results, with p values < 0.05 indicating statistical significance. Results The study included 30 patients, with an average age of 56.53 ± 11.52 years. Males accounted for 60% of patients. The most common symptoms included facial pain (63.33%), swelling (56.67%), and dental pain (53.33%). The palate was predominantly affected, with the majority showing palatal necrosis. Black eschar was observed in only 10 patients (33.33%), with nasal turbinates being the most frequently affected (5 patients, 16.67%), followed by palatal and facial eschars (2 patients, 6.67% each) and periorbital eschar (1 patient, 3.33%). Three patients (10%) had normal CT and MRI scans, and in the majority of our patients, both scans showed non-specific signs, such as bone erosion, sinus opacifications, and soft tissue thickening. The histopathological examination failed to detect fungi in 40% of the patients. Ten percent had a possible RMM, 30% had a probable RMM, and 60% had a proven RMM. Conclusion Atypical clinical presentations and/or negative imaging or laboratory test results are present in significant numbers of RMM patients. Therefore, mucormycosis should not be ruled out on the basis of the negative results of standard examinations. Successful diagnosis and prognosis require a high index of clinical suspicion, a detailed history, rigorous examination, and timely multidisciplinary examination.